2016
DOI: 10.14701/ahbps.2016.20.4.204
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoaneurysm of the splenic artery - an uncommon cause of delayed hemorrhage after pancreaticoduodenectomy

Abstract: Delayed post-pancreatectomy hemorrhage (PPH) is a relatively uncommon, but feared, complication after pancreaticoduodenectomy (PD). A splenic artery pseudoaneurysm is a rare cause of delayed PPH after a PD. This paper describes the case of a patient with PD used to treat a distal bile duct cholangiocarcinoma complicated with a clinically significant pancreatic fistula and secondary intraabdominal abscess. Computed tomography-guided drainage of the abscess was performed with an apparently favourable outcome; th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…PPH may originate from the following ( 15): (I) arterial or venous vessels; (II) anastomotic stoma (gastroenteric, jejunojejunal, or pancreaticoenteric); (III) resection areas (e.g., pancreas stump or retroperitoneum); (IV) gastric/duodenal ulcer or diffuse gastritis; (V) eroded and ruptured pseudoaneurysms; or (VI) hemobilia from previously placed endobiliary stents. Dumitru et al reported an uncommon cause of delayed hemorrhage after PD caused by a splenic artery pseudoaneurysm (16). To our knowledge, this is the first case report of output jejunal loop intussusception in the stomach that consequently caused PPH after PD.…”
Section: Discussionmentioning
confidence: 65%
“…PPH may originate from the following ( 15): (I) arterial or venous vessels; (II) anastomotic stoma (gastroenteric, jejunojejunal, or pancreaticoenteric); (III) resection areas (e.g., pancreas stump or retroperitoneum); (IV) gastric/duodenal ulcer or diffuse gastritis; (V) eroded and ruptured pseudoaneurysms; or (VI) hemobilia from previously placed endobiliary stents. Dumitru et al reported an uncommon cause of delayed hemorrhage after PD caused by a splenic artery pseudoaneurysm (16). To our knowledge, this is the first case report of output jejunal loop intussusception in the stomach that consequently caused PPH after PD.…”
Section: Discussionmentioning
confidence: 65%
“…In cases of embolization of the hepatic artery, hepatic failure is a major concern. However, if the gastric artery, splenic artery or the jejunal artery is ruptured, in most cases it can be embolized without much significance 22 …”
Section: Discussionmentioning
confidence: 99%
“…Post-operative complications include postoperative pancreatic fistula (POPF), hemorrhage, pseudoaneurysm and arteriovenous fistula. Delayed post-pancreatectomy bleeding refers to the bleeding at >24 h post-PD ( 17 , 23 ). The incidence of post-pancreatectomy bleeding has been estimated to be 4-16% and the mortality rate may be as high as 50% within 1-4 weeks ( 24-26 ).…”
Section: Discussionmentioning
confidence: 99%